Fungal glycans and the innate immune recognition - Barreto-Bergter, Eliana; Figueiredo, Rodrigo T. (Frontiers in Cellular and Infection Microbiology, 2014)
Polysaccharides such as α- and β-glucans, chitin, and glycoproteins extensively modified with both N- and O-linked carbohydrates are the major components of fungal surfaces. The fungal cell wall is an excellent target for the action of antifungal agents, since most of its components are absent from mammalian cells. Recognition of these carbohydrate-containing molecules by the innate immune system triggers inflammatory responses and activation of microbicidal mechanisms by leukocytes. This review will discuss the structure of surface fungal glycoconjugates and polysaccharides and their recognition by innate immune receptors.